Recent Advances in Audiological and Vestibular Research - Hatzopoulos, Stavros; Ciorba, Andrea (IntechOpen, 2022)
This book presents the latest information in audiological research with a strong emphasis on the vestibular system and the various types of hearing problems associated with otolith dysfunction. It is divided into two sections: "Vestibular Pathophysiological Features" and "Updates on Diagnosis and Therapy." Section 1 explores the pathophysiology of the vestibular pathways and Section 2 discusses several innovative approaches for a modern evaluation and rehabilitation of vestibular disorders. Chapters address such topics as tinnitus, signal transmission, vestibular testing, rehabilitation, and therapy, and audio-vestibular side effects of COVID-19 treatments.